Missionaries of health - Woy-Wojciechowski, Jerzy (Przewodnik Lekarza/Guide for GPs, 2010)
Summary of profiles of physicians-missionary was presented. The ones from the past like Albert Schweitzer (1875-1965), David Livingstone (1813-1873) from western countries, as well as polish like – St. Andrzej Świerad (980-1034), Michał Boym (1612-1659), Jan Tadeusz Krusiński (1675-1757) or blessed Jan Beyzym (1850-1912). From among many presently active phisicians on missions their activity in India (Adam Wiśniewski), Uganda (Wanda Błeńska), Zambia (Mirosława Góra) and Papua New Guinea (Jerzy Kuźma) was presented. Twenty one years of work of a phisician in Rwanda was outlined, archbishop Henryk Hoser, presently Ordynarius of Warsaw-Prague diocese. It was concluded that working as a physician on missions requires very valuble features in character.